Evaluasi Gameplay pada Game Fall Guys menggunakan Metode Heuristic Evaluation of Playability (HEP) - Haris Mahmudi; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Game Fall Guys was released on August, 2020. It was from Steam application. On TV program Liputan 6, August 4th, 2020, this new game was reported reaching a large amount of profit. In 24 hours, more than 1,5 million players played this game. This game got a positive respond from more than 20.000 players in Steam application. In addition, more than 100.000 players played the game because of some reasons such as funny characters and also attractive costumes they wear in the game. Although the first month game was released really hype and we could see many players played on Steam from August until now, the positive reviews from month to month were decreasing. Not only the positive reviews but also negative responses from players who were using cheat or challenges. To respond this, it is necessary to evaluate the gameplay using the Heuristic method then need 3 to 4 evaluators from the closest person to researcher which aim to see the advantages and disadvantages in terms of gameplay contained in the Fall Guys game.